The elasticity of taxable income for Germany and its sensitivity to the appropriate model - Clive Werdt (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2015)
This paper provides new empirical insights on the elasticity of taxable income for Germany. Using a rich panel of German income tax return data, the tax reforms of 2004 and 2005 are exploited implementing a new dynamic income model. Showing and discussing potential estimation problems of the most prominent model in the literature by Gruber and Saez (2002), this dynamic model delivers significant smaller estimates of the elasticity of taxable income. The overall estimate is 0.36 and robust against a number of sensitivity checks including non linear income controls. Elasticities differ between married and single assessed taxpayers with an elasticity of 0.17 for single and 0.44 for married taxpayers. These elasticities are similar to recent German results and considerablly smaller than recent results for the US from Weber(2014).
Keywords: C26; H21; H61; 330; taxable income elasticity; dynamic panel data estimation; income tax return data; administrative data